Development of a Multidimensional Additive Points System for Determining Access to Rheumatology Services. Issue 5 (August 2015) - White, Douglas; Solanki, Kamal; Quincey, Vicki; Minett, Andrew; Tam, Gordon; Doube, Alan; Naden, Ray
Abstract : Objective: In many countries, including New Zealand, the demand for rheumatology services exceeds their supply, resulting in some patients experiencing long delays or being denied access. The principal aim of this work was to create a validated, transparent, and fair system for determining access to rheumatology services. Methods: A panel of 5 rheumatologists, 6 primary care physicians, and 4 nurse specialists ranked a series of 25 clinical scenarios in order of priority to see a rheumatologist. Important determining factors were weighted in an iterative process to generate a multidimensional additive point score to determine access to rheumatology service. Results: The score comprises 6 domains of 2 to 4 items weighted to give a total score out of 100. The effect of the problem on the patient's life and role, the presence of an inflammatory rheumatic disease, appropriateness of current treatment, and the ability of the rheumatologist to influence the current symptoms and future prognosis were felt to be critical factors in determining access to the service. The score showed a strong correlation with the rankings agreed by the clinical panel, and the overall intraclass correlation coefficient for the rheumatologists was 0.698. Conclusions: Our score has face validity, is easy to perform, and has been assessed by an independent panel of rheumatologists as providing a fair system for determining access to rheumatology services. The system is acceptable to primary care physicians and has been adopted by our local primary care organizations.